"United we stand, divided we fall". The effects of US contestation on EU foreign climate policy ambition. Issue 4 (19th October 2020) - Petri, Franziska; Biedenkopf, Katja
ABSTRACT: A number of key governments' active diplomacy and leadership, including the European Union (EU) and the United States of America (USA), drove the adoption of the Paris Agreement on climate change in December 2015. Less than two years later, international climate politics looked very different: Former key proponents strongly contested climate policy, most prominently exemplified by President Trump's 2017 announcement to withdraw the USA from the Paris Agreement. Our analysis focuses on the EU's response to this hard contestation, as a central actor in the multilateral climate regime, the third-largest greenhouse gas emitter and an active proponent of achieving the Paris Agreement goals. We trace how the European Council, the Council of the EU, and the European Parliament (EP) responded to the USA's climate U-turn. Our qualitative content analysis finds that the EU overall pursued a rhetorical containment strategy by reinforcing its commitment to ambitious climate policy and the Paris Agreement.